On the Simplicity of Multigerms - Sinha, R. Oset; Ruas, M. A. S.; Atique, R. Wik (MATHEMATICA SCANDINAVICA, 2016)
We prove several results regarding the simplicity of germs and multigerms obtained via the operations of augmentation, simultaneous augmentation and concatenation and generalised concatenation. We also give some results in the case where one of the branches is a non-stable primitive germ. Using our results we obtain a list which includes all simple multigerms from C^3 to C^3.